HUBUNGAN FAKTOR PERSONAL DAN PENGAWASAN KERJA DENGAN TINDAKAN TIDAK AMAN PADA PEKERJA PENGELASAN DI BENGKEL LAS ABUN DESA SKIP KECAMATAN LUBUK PAKAM KABUPATEN DELI SERDANG - Rosita Ginting; Irmayani Irmayani; Anggi Isnani Parinduri; Muhammad Dani Harahap (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2020)
Work accidents are unwanted and unexpected events. Based on the Loss Caution Model theory, the direct causes of accidents are unsafe action and unsafe conditions. The purpose of this study was to analyze the relationship between personal factors and work supervision and unsafe action in welding workers at the Abun Las Workshop. This research type is quantitative with cross sectional research design. The population in this study were all welding workers, amounting to 34 people. The sampling technique was using the total sampling technique. The research instruments used in this study were questionnaires and observation sheets. The data obtained were processed by using the chi square statistical test with the degree of significance (Î±) = 0.05. The results of the analysis of the relationship between personal factors and work supervision with unsafe action on welding workers at the Las Abun Workshop are described as follows: personal factors (p value = 0.002) <Î± (0.05), this means that there is a significant relationship between personal factors (knowledge) and unsafe action on welding workers at the Las Abun Workshop, work supervision (p value = 0.038) <Î± (0.05), this means that there is a significant relationship between work supervision and unsafe action on welding workers at the Las Abun Workshop. Suggestions for the Abun Welding Workshop industry It is better if the Welding Workshop Industry has Occupational Safety and Health (K3) experts who can control and supervise all activities of welding workers at any time.